Uden for operahistoriens hovedspor: Berlioz’ Benvenuto Cellini og Schumanns Genoveva - Hesselager, Jens (Danish Yearbook of Musicology, 2006)
Outside the central developments of operatic history Berlioz’ Benvenuto Cellini and Schumann’s Genoveva The names of Hector Berlioz and Robert Schumann do not figure centrally in the history of opera. Yet both composers made highly ambitious debuts in the genre, at points in time when each were already considered to be amongst the leading composers – and music critics – of their age. The two debut-operas, Berlioz’ Benvenuto Cellini (1838) and Schumann’s Genoveva (1850), may in hindsight be seen as relatively inconsequential aberations from the main developments of the genre, but rather than being therefore historically uninteresting, this quality may, the article argues, instead be seen as a positive quality for the historian: an opportunity to study the openness of the historical situation. The two works are seen as representing original visions for a contemporary music drama – visions that differ significantly, not only from each other, but also from other visions (such as Wagner’s) that eventually became the more influential.